Comparison of Using Second-Generation Cryoballoon and Radiofrequency Catheter for Atrial Fibrillation Ablation in Patients With the Common Ostium of Inferior Pulmonary Veins - Li, Jia-hui; Xie, Hai-yang; Sun, Qi; Guo, Xiao-gang; Chen, Yan-qiao; Cao, Zhong-jing; Ma, Jian (Frontiers in Cardiovascular Medicine, 2022)
Aims: To compare the procedural outcomes of cryoballoon ablation (CBA) and radiofrequency ablation (RFA) in atrial fibrillation (AF) patients with the common ostium of inferior pulmonary veins (COIPV) and to explore the effect of COIPV on CBA performance through the assessment of anatomical factors. Methods: A total of 18 AF patients with COIPV were included. Pulmonary vein isolation (PVI) was performed with second-generation CBA or RFA. The anatomical characteristics of COIPV and procedural outcomes were collected. Results: The prevalence of COIPV was 0.82% in the enrolled population. PVI was achieved in all pulmonary veins (PVs) without any complications. The “tricircle” strategy was applied for RFA, and the segmental freeze strategy was performed for CBA. Compared with RFA, CBA had shorter procedural time (median: 53.0 vs. 78.0 min, p < 0.001) and longer fluoroscopy time (median: 13.5 vs. 6.0 min, p < 0.001). Higher ovality index of the ostium was seen in patients with ≥4 freezes in inferior PVs [IPVs; 0.95 (0.78–1.05) vs. 0.49 (0.21–0.83), p = 0.047]. During a median of 23.5 months of follow-up, the atrial arrhythmias-free survival after the procedure was comparable between CBA and RFA (p = 0.729). Conclusion: The second-generation CBA is an efficient and safe alternative for RFA in AF patients with COIPV. Anatomical characteristics of COIPV bring the challenge to the procedure performance of RFA and CBA.